2019
DOI: 10.1088/2515-7639/ab1795
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of graphene and related nanomaterials by dynamic spray-gun method: a new route to implement nanomaterials in real applications

Abstract: The dynamic spray-gun deposition method was developed in 2006 to fabricate field effect transistors based on random arrays of carbon nanotubes (CNTs) field effect transistors for gas sensing applications. Thanks to this deposition method, we were able to fabricate hundreds of operational devices in a reproducible way that were integrated in electronic chips. Following this first implementation, we decided to widen the application of the deposition technique to the field of Energy and specifically to the fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…GO films of ≈130 nm thickness were deposited using a spray‐gun technique on plain polyethylene terephthalate (PET) as well as on PET substrates pre‐coated with PEDOT:PSS. [ 34 ] Scanning electron microscopy (SEM) and atomic force microscopy (AFM) showed that the morphology of the as‐deposited GO layers is practically identical for both substrates. Therefore, only GO films on PET were considered in the following work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO films of ≈130 nm thickness were deposited using a spray‐gun technique on plain polyethylene terephthalate (PET) as well as on PET substrates pre‐coated with PEDOT:PSS. [ 34 ] Scanning electron microscopy (SEM) and atomic force microscopy (AFM) showed that the morphology of the as‐deposited GO layers is practically identical for both substrates. Therefore, only GO films on PET were considered in the following work.…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of the films, a spray‐gun technique was used. [ 34 ] PET and PEDOT:PSS/PET substrates (4–5 mm × 5–6 cm) used were placed on a hotplate set at 80 °C. The PEDOT:PSS/PET substrate was used as a control for investigating the adhesion and morphology of the films attained compared to those on the plain PET substrate.…”
Section: Methodsmentioning
confidence: 99%
“…[250,268] One form of spray-coating method, the dynamic spray-gun method, has been used to deposit graphene and its composites with other nanomaterials for various electronic and energy devices, including supercapacitors and random access memories. [269]…”
Section: Spray Coatingmentioning
confidence: 99%
“…45,46 The spray-gun is moved in the X-Y plane and the nozzle height over the substrate can be finely adjusted. The deposition is taking place in lines with length of 30cm and with a pitch of around 1cm to allow the best recovery of the sprayed cones 47 on a total width of 10cm. The precision for all the movements is around 100 μm.…”
Section: Electrode Preparation Preparation Of Electrodes Using Aqueou...mentioning
confidence: 99%